Climate extremes are critical to maize yield and will be severer in North China - Yan Wang; Yan-Jun Shen; Shui Yu; Xiaolong Zhang; Dengpan Xiao (Climate Risk Management)
With climate change, the frequency and intensity of climate extremes have increased significantly, exerting remarkable impacts on agricultural production in China. Irrigation, as an efficient agricultural management approach to maintaining the crop yield, was widely but unevenly implemented in China. Elucidating the impacts of climate change on maize yield and the role of irrigation in mitigating the climate change impacts on maize yield is critical to enhance the resilience of the national food system. Here, the key growing period and the sensitive meteorological indicators to maize yield variation in two major maize producing regions of China were revealed using the multiple regression models. The results indicate that the reproductive growing period and the precipitation-related indicators are more prominent for the maize yield variation in the North China Plain, whereas in Northeast China Plain, the vegetative growing period and the temperature-related indices contribute more to the maize yield. Among all meteorological indicators, the heat degree days and the consecutive dry days are the most influential meteorological factors to maize yield, and the heat degree days are projected be increasing drastically in the future, bring more heat threats to the maize yield. Result show that agricultural irrigation could significantly mitigate the dependence of maize yields variation on climate change, the determination coefficients of climate indices on maize yield decreased by 0.10 and 0.15 for the North China Plain and Northeast China Plain as the irrigation intensity increased. Adaptable solutions concerning the impact of extreme climates and the construction of agricultural irrigation facilities should be taken into consideration to cope with climate change and ensure the food security.